Ethics in financial planning: Analysis of ombudsman decisions using codes of ethics and fiduciary duty standards. Issue 3 (August 2022) - Richards, Daniel W; Ahmed, Abdullahi D; Bruce, Kenneth
Scandals show that ethics is an important topic in financial planning. Our research analyses 212 financial ombudsman decisions (2013–2018) to understand the nature of financial planning misconduct in complaint decisions. We develop a coding structure to ascertain what professional conduct involves and then use content analysis and cluster analysis to identify the aspects of professional conduct occurring in these misconduct decisions. Diligence, acting in the client's best interest and having no reasonable basis for advice are interconnected elements in over half of these decisions. Secondary elements are misleading statements, conflicts of interest and disclosure. Analysis of decisions involving fiduciary duty showed that financial planners failed to ascertain a client's circumstances and did not form advice based on their client's information. As financial planning professionalises, future research, financial planning education, policy and practice should address these issues. JEL Classification:D14, G20, G50